Study of the Effects of High Glucose Concentration in Culture Media on Osteoblast Viability and Integrin Gene Expression on Titanium Surfaces: An In Vitro Study - จึงกิจธนวัฒน์ วสุพล; เสรีเชษฐพงษ์ ประเวศ; วรีเจิ่งประภากร วรีย์รัตน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to investigate the effects of glucose concentration in culture media on osteoblast viability and integrin expression on titanium surfaces under in vitro conditions. Normoglycemic and hyperglycemic environments observed in diabetic patients were simulated. Primary human alveolar osteoblasts obtained from alveolar bone were cultured in Dulbecco’s Modified Eagle Medium supplemented with 10% fetal bovine serum, 1% antibiotic agents, and 1% L-glutamine. Cells at passage 3 were used for the experiments. The osteoblasts were then seeded onto prepared titanium discs and divided into two groups according to glucose concentration: a low-glucose group (5.5 mmol/L) and a high-glucose group (25 mmol/L). Cells were maintained under controlled conditions at 37 °C in a humidified atmosphere containing 5% CO2. Osteoblasts were isolated from three independent donors, and experiments for each donor were performed in triplicate. Cell viability was evaluated using the MTT assay at 24 and 48 hours. The expression of integrin genes (α5 and β1) was assessed at 24 hours using reverse transcription polymerase chain reaction (qRT-PCR). The results demonstrated that osteoblast viability and proliferation in the high-glucose group were not significantly different from those in the low-glucose group (P>0.05) at both time points. Similarly, the expression levels of integrin α5 and β1 at 24 hours showed no significant differences between the two groups (P>0.05). These findings suggest that short-term exposure to elevated glucose alone may not be sufficient to impair osteoblast survival or proliferation or alter early integrin-mediated cell adhesion on titanium surfaces in vitro. The impact of diabetes on bone–implant integration may instead involve additional pathophysiological factors, such as the accumulation of advanced glycation end products, oxidative stress, and chronic inflammation, which warrant further investigation. The knowledge gained from this study may serve as baseline information for designing future research and for treatment planning in implant dentistry for patients with systemic conditions such as diabetes.